Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Pendekatan Kontekstual: Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Pendekatan Kontekstual - Agung, Agung Setio Nugroho (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2023)
This study aims to produce interactive mathematics learning media based on a contextual approach and determine the quality of interactive mathematics learning media from the aspects of validity, and practicality. The type of research carried out is development research. The development model used is the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. This learning media was created using PowerPoint software, IspringSuite and also Apk Builder Pro. The results showed that the interactive mathematics learning media developed was included in the